A new methodology to evaluate system‐level performance of explosion suppression systems. Issue 2 (24th October 2017) - Chao, Jenny; Dorofeev, Sergey
Abstract : A parametric experimental study was performed to understand the effect of various factors on the explosion suppression phenomenon. Full‐scale suppression experiments were conducted in FM Global's 2.5 and 25 m 3 vessels. Either quiescent propane‐air or cornstarch‐air explosions were suppressed using a 2.5, 5, 10, or 50 L suppressant bottle, filled with sodium bicarbonate and pressurized with nitrogen to approximately 62 bar. The growth of the suppressant cloud in the open atmosphere was also measured in conjunction with the pressure drop in each size of suppressant bottle. From these results, it was found that an expanding flame must be entirely enveloped by suppressant for successful suppression of the flame to occur. Based on this concept, a simple physics‐based model was developed to determine the maximum protected throw distance, surface area, and volume of a single suppressant bottle (as part of a suppression system). This can be easily scaled to larger volumes than what was used in the experiments. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 237–247, 2018